Practical Manual of Interventional Cardiology - Kini, Annapoorna; Sharma, Samin; Narula, Jagat; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
This practical handbook is based on an internal working manual developed by staff and fellows at Mount Sinai Heart Cardiovascular Catheterization Laboratory, renowned for its high-volume and low complication complex coronary procedures. The Practical Handbook of Interventional Cardiology captures the knowledge and methodological know-how from leaders in interventional cardiology, it intends to guide users in a stepwise, methodical and practical approach through various cardiac interventional procedures in order to achieve maximum patient safety and improved outcomes. From patient selection, preoperative work-up, setting up equipment to step-by-step illustrations of various procedural details and troubleshooting, this handbook captures all the details necessary to perform the simplest to the most complex cardiac interventions. The book is designed for cardiologists and trainees who desire an efficient way to review the steps of various cardiac interventional procedures and a quick, reliable reference for everyday use.
Part I: Interventional Basics -- Basics of Radiation Safety -- Achieving Perfect Vascular Access -- The Perfect Shot: Angiographic Views for the Interventionalist -- Physiological assessment during interventional procedures -- Antiplatelet and Antithrombotic therapy in PCI -- Patient Selection and Appropriateness -- Guiding Catheter Selection -- Guidewire Properties and Selection -- Assessment of Lesion Severity (Intravascular Ultrasound, Optical Coherence Tomography, NIRS and Beyond) -- Basics of Intracoronary Devices -- Hemodynamic assessment: Right Heart Catheterization, Pulmonary Hypertension, Left-To-Right Shunt, And Constriction -- Hemodynamic Assessment of Aortic/Mitral Stenosis And Regurgitation -- Vascular Closure Devices and Complications -- Part 2: Coronary Intervention -- Basics of Intervention -- Difficult Stent Delivery -- Bifurcation Lesions -- Ostial Lesion Interventions -- Left Main Coronary Interventions -- Chronic Total Occlusions -- ACS: STEMI/ Non-STEMI Intervention -- Coronary Artery Bypass Graft Interventions -- Calcific Lesion Interventions -- Coronary Complications Of Percutaneous Coronary Interventions -- Radial Coronary Interventions -- Part 3: Special Procedures -- Advanced Hemodynamic Support -- Aortic Valve Interventions-Balloon Aortic Valvuloplasty/ Transcatheter Aortic Valve Implantation -- Balloon Mitral Valvuloplasty -- Alcohol Septal Ablation -- Pericardiocentesis and Balloon Pericardiotomy -- Contrast-Induced Nephropathy Post Percutaneous Interventional Procedures.
Keywords: Medicine; Interventional radiology; Cardiology; Medicine & Public Health; Cardiology; Interventional Radiology; Electronic books